The potential of lipocalin-2/NGAL as biomarker for inflammatory and metabolic diseases. (17th November 2015) - Abella, Vanessa; Scotece, Morena; Conde, Javier; Gómez, Rodolfo; Lois, Ana; Pino, Jesús; Gómez-Reino, Juan J.; Lago, Francisca; Mobasheri, Ali; Gualillo, Oreste
Abstract: Lipocalin-2 (LCN2), also known as neutrophil gelatinase-associated lipocalin (NGAL), is a secreted glycoprotein that belongs to a group of transporters of small lipophilic molecules in circulation. LCN2 has been recently characterized as an adipose-derived cytokine. This adipokine is believed to bind small substances, such as steroids and lipopolysaccharides, and has been reported to have roles in the induction of apoptosis in hematopoietic cells, transport of fatty acids and iron, modulation of inflammation, and metabolic homeostasis. Recently, LCN2 has emerged as a useful biomarker and rheumatic diseases. This review provides an overview of LCN2 in inflammation, immunity, and metabolism.